RESEARCH ON THE DEVELOPMENT OF IRRIGATION PROCEDURES FOR SOYA CULTIVARS ON DESIRABLE SOILS PROTECTED FROM DEFLATION BY BACKHOE BARRIERS (European Journal of Interdisciplinary Research and Development, 2025)
Research was conducted to study the irrigation regimes of soybean varieties in areas protected from wind erosion by cover barriers in 2021-2023 on deflated barren soils of the "At the Level of Opportunity" farm in the Koson district of the Kashkadarya region.